The effect of feed composition on the solubility and dispersibility of coconut-based non-dairy creamer - 318087 Mariani Abdul Hamid (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2007